Physical properties of juvenile and mature sycamore maple (Acer pseudoplatanus L.) wood from Medvednica region Fizička svojstva juvenilnoga i zrelog drva gorskog javora (Acer pseudoplatanus L.) s područja Medvednice - Sedlar, Tomislav; Sinković, Tomislav; Trajković, Jelena; Hasan, Marin; Ištok, Iva; Šefc, Bogoslav (2019)
Physical properties play an important role in predicting wood quality. The aim of this study was to investigate radial variations in physical properties of sycamore maple (Acer pseudoplatanus L.) wood, to determine the border between juvenile and mature wood and to compare them with analogous variations in beech wood. Radial variation of density in absolutely dry condition, maximum density, nominal density, longitudinal, radial, tangential and volumetric shrinkage, maximum moisture content and annual ring width on five sycamore maple trees from Medvednica region in Croatia were determined. Observing the trend curves and comparing average values of physical properties, different zones in the cross section of the trunk were determined. In the first zone, from the pith to about 30th annual ring, more rapid changes in physical properties occurred. It is followed by transitional zone, which ranges roughly from 30th to 40th annual ring. After 40th annual ring, less pronounced changes in measured physical properties occurred. Sharp boundary between juvenile and mature wood zones could not be determined. According to the results, the first zone is considered to be juvenile wood, while mature wood starts after the 30th annual ring.
Fizička svojstva drva imaju važnu ulogu u predviđanju njegove kvalitete. Cilj ovog rada bio je istražiti radijalne varijacije fizičkih svojstava drva gorskog javora (Acer pseudoplatanus L.), utvrditi granicu između juvenilnoga i zrelog drva te ih usporediti s odgovarajućim varijacijama u drvu bukve. Utvrđene su radijalne varijacije gustoće u apsolutno suhom stanju, gustoća pri maksimalnom sadržaju vode, nominalna gustoća, longitudinalno, radijalno, tangentno i volumno utezanje, maksimalni sadržaj vode i širina godova u drvu pet stabala gorskog javora s Medvednice u Hrvatskoj. Iz dobivenih krivulja i usporedbe prosječnih vrijednosti fizičkih svojstava drva utvrđene su različite zone na poprečnom presjeku debla. U prvoj zoni, od srčike do približno 30. goda, vidljive su znatnije promjene fizičkih svojstava drva. Slijedi prijelazna zona, koja se otprilike proteže od 30. do 40. goda. Nakon 40. goda promjene fizičkih svojstava drva manje su vidljive. Oštru granicu između zona juvenilnoga i zrelog drva nije moguće odrediti. Na temelju dobivenih rezultata pretpostavljeno je da je prva zona juvenilno drvo, a nakon 30. goda počinje zrelo drvo.
Bibliografija: 27 jed.
Abstract ; Sažetak.
Keywords: Gorski javor -- Fizička svojstva -- Radijalne varijacije; Medvednica